Neutrophil surface adhesion molecule and toll like receptor dynamics in crossbred cows suffering from Staphylococcus aureus subclinical and clinical mastitis (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The present study was an attempt to delineate the roles played by the neutrophil surface adhesion molecules and toll like receptors (TLRs) in crossbred cows suffering from Staphylococcus aureus subclinical and clinical mastitis.Materials and methods:  Thirty six Karan Fries (KF) cows were categorized into three groups namely healthy (n=12), subclinical mastitis (SCM; n=12) and clinical mastitis (CM; n=12) after screening 146 cows. The grouping was done based on evaluation of collected milk samples by routine procedures like Californian Mastitis Test (CMT) scoring, microscopic counting of milk cells (SCC), bacterial culture of milk samples and observing gross changes in milk. Culture of milk and blood was done for the identification of Staphylococcus aureus subclinical and clinical mastitis. Results: Healthy cows expressed significantly (P